ANALISIS KINERJA PERUSAHAAN PRE-SEASONED EQUITY OFFERINGS - Heni Kurniawan; Ch. Rusiti (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2004)
The aim of this research is to prove whether earnings management persists in prior to Seasoned Equity Offerings (SEO) at the Jakarta Stock Exchange. This research is conducted by comparing financial performances during periods before SEO of companies which execute seasoned equity offerings to those which did not. Samples for this research are companies listed in the Jakarta Stock Exchange during 1997 –2002. The hypothesis for this research is that the financial performances of companies executing SEO is higher than those companies not executing SEO. Proxy for SEO is the event of right issue. Current Ratio (CR), Debt Equity Ratio (DER), Return On Investment (ROI) ratio, Net Profit Margin (NPM) ratio, and Operating Profit Margin (OPM) ratio are used to assess financial performance. 47 companies make thesample of companies executing SEO during 1997 – 2002. For comparison, non-SEO companies are chosen from companies of similar industries and size as those of SEO companies.This research provides evidence that, on average, performances of companies executing SEO are higher than those companies not executing SEO, even though the difference is statistically insignificant. The conclusion for this research is that there are no significant financial performance differences between SEO companies and non SEO companies in the period prior to SEO. The indications of earnings management inthe event of SEO is found in a small numbers of companies.Keywords: Seasoned Equity Offerings, Right Issue, Earnings Management, and Jakarta Stock Exchange